STRATEGI KOMUNIKASI PEMASARAN DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN KARIMUN DALAM MENARIK MINAT PENGUNJUNG WISATA DI PANTAI LUBUK - Rizky Frahanandani; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Lubuk Beach is a leading beach in Karimun Regency, and is well known by tourists. Lubuk Beach has the characteristics of rocks and culinary highlights to attract tourists to visit, the Department of Tourism and Culture also makes Lubuk Beach as the top 13 favorite tourist attraction in Karimun district, but in attracting tourist visitors an effective marketing communication strategy is needed to create attraction . The purpose of this study is to determine the segmentation, targeting, and positioning of the Karimun Regency Tourism and Culture Office in attracting tourist visitors in Lubuk Beach, and to find out the elements of marketing communication carried out by the Karimun Regency Tourism and Culture Office, and to know the involvement Pokdarwis in assisting the Culture and Tourism Office of Karimun Regency in attracting tourism visitors on Lubuk Beach.This study used qualitative research methods. The subjects in this study consisted of six subjects as informants through purposive techniques. Data collection techniques are grouped into three parts, namely: Observation, interview, and documentation. The data analysis technique in this study uses the Miles and Huberman interactive data models. Checking the validity of the data using the technique of extending participation and triangulation.The results showed that the communication strategy carried out by the Office of Tourism and Culture of Karimun Regency was to determine the Segmentation based on gender, age, origin, education and occupation. By targeting 5 thousand visitors each year, and positioning by making the tag line "interesting beach", so the promotion process can run even better so that visitors are interested. The form of promotion carried out by the Office of Tourism and Culture of Karimun Regency with several media namely: events, booklets, social media, websites, and brochures. Pokdarwis involvement in helping the Karimun Regency Tourism and Culture Office with the cooperation and promotion of tourism objects and the management of Lubuk Beach attractions so that they become tourist attractions. Keywords: Marketing, Media, Visitor Intere